HUBUNGAN PENGGUNAAN GADGET DENGAN KUANTITAS DAN KUALITAS TIDUR ANAK KELAS 4-6 SD HKBP PARDAMEAN - Roito Hutabarat; Dior Manta Tambunan (Indonesian Trust Nursing Journal, 2026)
The use of gadgets among elementary school children has increased significantly along with the development of digital technology. Excessive gadget use has the potential to disrupt children’s physiological needs, particularly sleep quantity and sleep quality, which play an important role in growth, learning concentration, and physical and mental health. The objective This study is determine the relationship between gadget use and the quantity and quality of sleep among students in grades 4–6 at HKBP Pardamean Elementary School, Medan. The methodes This study employed a quantitative design with a cross-sectional approach. The popula tion consisted of all students in grades 4–6 at HKBP Pardamean Elementary School, totaling 50 students. A total sampling technique was used, in which the entire population was included as the sample. The instruments used were a 21-item Likert-scale gadget use questionnaire, the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality, and sleep duration measurement to assess sleep quantity. The results of the Spearman’s rho correlation test showed a value of (p > 0.05), indicating that there was no significant relationship between gadget use and the quantity and quality of sleep among students in grades 4–6 at HKBP Pardamean Elementary School, Medan. the conculsion is Gadget use among the respondents was not statistically proven to have an effect on the quantity and quality of sleep in school-aged children. It is recommended that future studies include additional variables such as parenting style, academic stress, and sleep environment as potential influencing factors.